2010
DOI: 10.1073/pnas.1006162107
|View full text |Cite|
|
Sign up to set email alerts
|

Liver X receptor β and thyroid hormone receptor α in brain cortical layering

Abstract: In the past year, two members of the nuclear receptor family, liver X receptor β (LXRβ) and thyroid hormone receptor α (TRα), have been found to be essential for correct migration of neurons in the developing cortex in mouse embryos. TRα and LXRβ bind to identical response elements on DNA and sometimes regulate the same genes. The reason for the migration defect in the LXRβ −/− mouse and the possibility that TRα may be involved are the subjects of the present study. At E15.5, expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
30
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 48 publications
2
30
0
Order By: Relevance
“…However, in vivo, we found no immunostaining of LXRβ in neurons of the substantia nigra in adult mice. Because the LXRβ antibody has been extensively tested in the brain where it stains neurons in the fetal and neonatal brain (23,24), we are confident in our finding that LXRβ is not expressed in adult neurons, and conclude that an LXR agonist may not directly regulate the expression of α-synuclein in dopaminergic neurons in vivo. However, because nuclear receptors can be modified posttranscriptionally, we cannot exclude the possibility that some modification of the N terminus of LXRβ (which was the site of the epitope used in raising the antibody) has occurred in the mature neurons that leads to loss of the ability of the antibody to recognize the receptor.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…However, in vivo, we found no immunostaining of LXRβ in neurons of the substantia nigra in adult mice. Because the LXRβ antibody has been extensively tested in the brain where it stains neurons in the fetal and neonatal brain (23,24), we are confident in our finding that LXRβ is not expressed in adult neurons, and conclude that an LXR agonist may not directly regulate the expression of α-synuclein in dopaminergic neurons in vivo. However, because nuclear receptors can be modified posttranscriptionally, we cannot exclude the possibility that some modification of the N terminus of LXRβ (which was the site of the epitope used in raising the antibody) has occurred in the mature neurons that leads to loss of the ability of the antibody to recognize the receptor.…”
Section: Discussionmentioning
confidence: 67%
“…Activation of LXRs leads to release of associated corepressor proteins and interaction with coactivators, resulting in target gene activation (17)(18)(19). LXRα, which is expressed primarily in adipose tissue, liver, and intestine, plays an important role in cholesterol homeostasis, whereas LXRβ (20-22) has key functions in the CNS and the immune system.We have previously shown that LXRβ expression is involved in formation of superficial cortical layers and migration of later-born neurons in embryonic mice (23,24), and that LXRβ is essential for maintenance of motor neurons in the spinal cord and dopaminergic neurons in the substantia nigra (25, 26). The substantia nigra and motor neurons in the spinal cords of LXRβ −/− mice are normal until the mice are 6 mo of age.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Primary antibodies were detected with donkey antigoat Cy3 (1:400; Jackson ImmunoResearch), donkey antirabbit FITC (1:400; Santa Cruz Biotechnology), donkey antichicken FITC (1:400; Jackson ImmunoResearch), and donkey antimouse Cy3 (1:400; Jackson ImmunoResearch). Sections were later counterstained with Vectashield mounting medium containing 4', 6'-diamidino-2-phenylindole (DAPI) (Vector) to label nuclei (43,44).…”
Section: Methodsmentioning
confidence: 99%
“…We previously showed that LXRβ expression is essential for the maintenance of motor neurons in the spinal cord and dopaminergic neurons in the substantia nigra (25,26). More recently, we found that LXRβ plays a specific role in cortical lamination and is essential for radial migration of later-generated neocortical neurons in embryonic mice (27,28).…”
mentioning
confidence: 91%